Motion state-based data delivery scheme of delay tolerant mobile sensor networks - YANG Kui-wu1; ZHENG Kang-feng1; YANG Yi-xian1; GUO Shi-ze1; WU Bin1 (Tongxin xuebao)
A motion state-based data delivery scheme（MSD） was proposed for delay tolerant mobile sensor network.By using the broadcasting signal of base station on the frequency of f1,sensor nodes could compute their own motion stated and delivery probabilities which provided the bases for messages transmitting between nodes on the frequency of f2.In order to improved network performance,MSD employed the message survival time and prior forwarding mechanism of own messages to manage the message queue.Simulation results show that the proposed MSD data delivery scheme has a higher message delivery ratio with lower transmission cost and less data delivery delay than other DTMSN（delay tolerant mobile sensor networks） data delivering approaches.